FILSAFAT RIEK LIAU: MENILIK FENOMENA PERJUDIAN PADA RITUAL WARA DI KABUPATEN BARITO UTARA - Vedanti, Kunti Ayu; Sasmita, Rinaldi (Satya Widya: Jurnal Studi Agama, 2023)
One of the processions in the Wara Ritual, knowns as Riek Liau, is often identified as gambling by people in North Barito Regency, even though it is clear in the Criminal Code article 303 that gambling is not justified in any form. Gambling on the Wara Ritual is a phenomenon that has generated controversy in society. One of the contributing factors is the general public's lack of understanding of Riek Liau's philosophy. Based on this phenomenon, further research related to Riek Liau's philosophy is important to do. This research was conducted in Lahei District with qualitative methods with a research time of 6 (six) months using observation and interview techniques, as well as using supporting data from related literature sources. This research then finds Riek Liau's mythology, implementation and philosophy of the gambling phenomenon in the Wara Ritual, that gambling is accordance to Riek Liau's philosophy as a game of holy spirits. Likewise, the Wara Ritual is a sacred death ritual for Hindu Kaharingan people and a symbol of belief in Almighty God.